2014
DOI: 10.1063/1.4894148
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a thermally persistent h.c.p. solid-solution phase in the Ni-W system

Abstract: Although the accepted Ni-W phase diagram does not reveal the existence of h.c.p.-based phases, h.c.p.-like stacking sequences were observed in magnetron-co-sputtered Ni-W thin films at W contents of 20 to 25 at. %, by using transmission electron microscopy and X-ray diffraction. The occurrence of this h.c.p.-like solid-solution phase could be rationalized by first-principles calculations, showing that the vicinity of the system's ground-state line is populated with metastable h.c.p.-based superstructures in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…These energies were used for drawing the phase diagram at zero kelvin and Ni 4 W and Ni 8 W phases were found to be stable. These findings were confirmed by Kurz et al [14,15], who found Ni 8 W (bct Pt 8 Ti type) and Ni 4 W (Ni 4 Mo type) phases to be stable, but Ni 3 W phase (hcp-Cu 3 Ti type) to be at least metastable.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…These energies were used for drawing the phase diagram at zero kelvin and Ni 4 W and Ni 8 W phases were found to be stable. These findings were confirmed by Kurz et al [14,15], who found Ni 8 W (bct Pt 8 Ti type) and Ni 4 W (Ni 4 Mo type) phases to be stable, but Ni 3 W phase (hcp-Cu 3 Ti type) to be at least metastable.…”
Section: Introductionsupporting
confidence: 79%
“…The result was that Ni 3 W compound was found from samples annealed after deformation, therefore this compound could be metastable, at least at 1 373 K. During annealing at 1 373 K the amount of Ni 3 W diminishes, which means metastability of the phase or that the temperature is over the dissociation temperature. The annealing temperature 1 373 K is over 850 K, where Ni 3 W forms according to Kurz [14,15]. The stability and metastability ratios of Ni 3 W phase are related to different temperatures and conditions: Ni 3 W is stable at lower temperatures and metastable at higher temperatures, which was reflected in the calculations made.…”
Section: Phase Diagram and Activity Datamentioning
confidence: 92%
See 3 more Smart Citations